Nanofibrous Biomaterial Containing Raw‐Propolis Particles Encapsulated by PLA/PBS for Wound Dressing Application - Ecem Özdilek; Sema Samatya Yilmaz; Hüseyin Uzuner; Ayse Aytac (Macromolecular Materials and Engineering)
Abstract The hollow nanofibrous materials were obtained by successfully encapsulating different rate raw‐propolis particles (5%, 10%, and 15%) with hydrophobic polylactic acid/polybutylene succinate (PLA/PBS, 93/7, w/w) blend. No purification process such as extraction was applied to raw propolis and propolis was used as raw. High liquid absorbing capacity values between 400 and 600% were observed owing to the hollow core of the nanofiber. Scanning electron microscopy (SEM) surface images of hollow nanofibers became transparent, and it was seen that the fiber diameters were thickened. The tensile stress of 5% propolis‐encapsulated biomaterial exhibited the highest value of 1.25 MPa. High antibacterial activity was observed especially against Staphylococcus aureus (S. aureus) at the end of the 24th and 48th h with the dispersion of raw‐propolis particles in the core of propolis‐encapsulated all fibrous materials. However, it was seen that the use of propolis in its raw form caused the emergence of toxic effects. It was reported that hollow biomaterials containing raw‐propolis particles encapsulated by PLA/PBS could not be used as wound dressings due to insufficient fibroblast cell viability. So, it was suggested that pure hollow PLA/PBS fibrous mats could be used as skin tissue scaffolds.